The influence of changing the girder’s length and high’ as well as zone’s width on the amount of welded girder’s deflection - Palić, Vlastimir (Journal of Production Engineering, 1989)
In this paper, a three-factorial extreme experiment was conducted to determine the influence of changing the girder’s length, height, and the width of the zone on the amount of deflection in welded girders. The thickness of the girder’s sheet metal was 6 mm